2019
DOI: 10.7567/1882-0786/ab03eb
|View full text |Cite
|
Sign up to set email alerts
|

Sub-milliampere-threshold continuous wave operation of GaN-based vertical-cavity surface-emitting laser with lateral optical confinement by curved mirror

Abstract: The continuous wave operation of a gallium-nitride-based vertical-cavity surface-emitting laser (GaN-based VCSEL) that uses boron ion implantation for lateral current confinement and a curved mirror for lateral optical confinement was investigated. The threshold current was 0.25 mA (Jth = 3.5 kA cm−2) for a 3 μm diameter current aperture at room temperature and the lasing wavelength was 445.3 nm. This is the lowest threshold current recorded for a GaN-based VCSEL. This result is considered to be a milestone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“… 2 The VCSEL market will be further expanded when visible-emitting GaN-based VCSELs are commercialized. This will soon be a reality based on the recent immense improvement in performance 3 8 enabled by advances in thermal management, 3 , 6 , 9 optical confinement, 5 , 10 , 11 mirror reflectivity, 8 , 10 , 12 and electrical injection. 7 , 13 Part of these advances may also boost the development of ultraviolet (UV) AlGaN-based VCSELs, sources with a higher brightness than LEDs.…”
mentioning
confidence: 99%
“… 2 The VCSEL market will be further expanded when visible-emitting GaN-based VCSELs are commercialized. This will soon be a reality based on the recent immense improvement in performance 3 8 enabled by advances in thermal management, 3 , 6 , 9 optical confinement, 5 , 10 , 11 mirror reflectivity, 8 , 10 , 12 and electrical injection. 7 , 13 Part of these advances may also boost the development of ultraviolet (UV) AlGaN-based VCSELs, sources with a higher brightness than LEDs.…”
mentioning
confidence: 99%
“…However, unlike their NIR counterparts, visible-light VCSELs are still immature for the aforementioned fabrication challenges. Recently, some of these challenges have been addressed by using novel DBR designs based on curved mirrors or nano-porous n-type GaN to create blue-and green-light VCSELs [36][37][38]. Moreover, a quantum-dot-based VCSEL design that can be used to produce laser light in the blue-green range has also been previously demonstrated [39].…”
Section: Displays Augmented and Virtual Realitymentioning
confidence: 99%
“…The high reflectance of the embedded DBR structure can provide a high-quality factor of the lasing peak in the VCSEL devices. For the embedded DBR structures, the epitaxial AlGaN/GaN [3,4], AlN/GaN [5], and AlInN/GaN [6] DBR structures have been reported that have high reflectivity at the emission wavelength region of the InGaN active layers. All dielectric DBR VCSEL structures have been reported that are deposited on curved mirror of the sapphire substrate [7], on GaN after sapphire lift-off process [8], and as the epitaxial lateral overgrowth mirror [9].…”
Section: Introductionmentioning
confidence: 99%